Keeping it small, polar, and non-flat: diversely functionalized building blocks containing the privileged 5, 6, 7, 8-tetrahydro[1, 2, 4]triazolo[4, 3-a]- and [1, 5-a]pyridine cores. Issue 9 (2nd March 2016) - Mishchuk, Alexander; Shtil, Natalia; Poberezhnyk, Mykola; Nazarenko, Konstiantyn; Savchenko, Timur; Tolmachev, Andrey; Krasavin, Mikhail
Graphical abstract: Abstract: Six sets of functionalized building blocks based on 5, 6, 7, 8-tetrahydro[1, 2, 4]triazolo[4, 3- a ]pyridine as well as 5, 6, 7, 8-tetrahydro[1, 2, 4]triazolo[1, 5- a ]pyridine cores have been prepared. These compounds are non-flat, bicyclic heterocycles that are likely to find utility as privileged motifs for lead-like compound design. One set of building blocks, (5, 6, 7, 8-tetrahydro[1, 2, 4]triazolo[4, 3- a ]pyridin-6-ylmethyl)amines, proved useful as a scaffold for developing compounds that stimulate glucagon-like peptide-1 (GLP-1) secretion and are novel anti-diabetes drug leads.